The Political Economy of Health Services Provision and Access in Brazil - Mushfiq Mobarak, Ahmed; Rajkumar, Andrew Sunil; Cropper, Maureen (World Bank, Washington, DC, 2012)
The authors examine the impact of local politics and government structure on the allocation of publicly subsidized (SUS) health services across municipios (counties) in Brazil, and on the probability that uninsured individuals who require medical attention actually receive access to those health services. Using data from the 1998 PNAD survey they demonstrate that higher per capita levels of SUS doctors, nurses, and clinic rooms increase the probability that an uninsured individual gains access to health services when he, or she seeks it. The authors find that an increase in income inequality, an increase in the percentage of the population that votes, and an increase in the percentage of votes going to left-leaning candidates are each associated with higher levels of public health services. The per capita provision of doctors, nurses, and clinics is also greater in counties with a popular local leader, and in counties where the county mayor and state governor are politically aligned. Administrative decentralization of health services to the county decreases provision levels, and reduces access to services by the uninsured, unless it is accompanied by good local governance.